Remote camping along the Ningaloo Coast, Western Australia: relationship between management and the variables of visitor preferences, resource use and environmental impacts - Lewis, Anna Rose (Curtin University, 2013)
The aim of this multidisciplinary study was to identify relationships between level of management oversight and the variables of visitor preferences, resource use and environmental impacts at remote coastal campsites along the Ningaloo coast, Western Australia. Significant differences existed for all three variables, determined from four statistically-derived campsite clusters. This thesis demonstrates the importance of management practices to specific types of environmental impact and expands methodological and theoretical knowledge for semi-arid, vehicle accessible environments.